Exploring Online Classroom Interaction Pattern: Students’ Perception of Online Classroom - Fajar Kresno Alwiyono; Ahmad Munir; Syafi'ul Anam (Universitas PGRI Madiun, 2021)
In this Covid-19 Pandemic situation, the teaching and learning process has different modes. Recently, teaching and learning have been done by online mode. In Indonesia, most of the teacher uses WhatsApp application as their main platform to be a bridge for teaching and learning. However, the teacher needs to use the other platform to assist the students especially in learning English. This research tried to investigate the online classroom interaction and the students’ perception toward online classroom interaction. Classroom interaction became a vital thing for the students in developing their English skills. This research used a qualitative method for interpreting the data. The findings showed that the IRF strategy was used by the teacher. Furthermore, teacher–whole classroom, and teacher–student interaction also happened in the finding of the research. Moreover, the students here had a good perception of online classroom interaction. Yet, they felt that offline meeting was also important. Hence, the students hoped that it could be done balance between online and offline classroom. Besides that, even the students claimed that they prefer online classroom, yet there were some challenges that students faced such as insufficient internet data, unstable signals, and crowded written platform.